Resin composition for low-loss high-Tg white copper-clad plate, prepreg, copper-clad plate and preparation method of resin composition

By using alicyclic epoxy resin, hydrocarbon resin and polyphenylene ether resin composition, the ratio and process are optimized, and the dielectric performance of existing white copper clad plates is solved, and copper clad plates with low dielectric loss, high Tg and high whiteness are achieved, which are suitable for high-frequency and high-speed MiniLED applications.

CN119842207APending Publication Date: 2025-04-18SHANTOU ULTRASONIC COPPER CLAD LAMINATE TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510074159.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing white copper clad plate has insufficient dielectric performance and is difficult to meet the needs of circuit board backlight applications such as high-frequency and high-speed MiniLED.

Method used

Using a composition of alicyclic epoxy resin, hydrocarbon resin and polyphenylene ether resin, a resin composition with low dielectric loss, high glass transition temperature and high whiteness is prepared for the preparation of copper clad plates through optimized proportion and process treatment.

Benefits of technology

It realizes the low dielectric loss, high Tg and high whiteness performance of copper clad plate, and is suitable for high frequency and high speed applications, significantly improving the reliability and processing performance of the plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of copper-clad plates, and particularly relates to a resin composition for a low-loss high-Tg white copper-clad plate, a prepreg, a copper-clad plate and a preparation method of the copper-clad plate. The invention provides a resin composition for a white copper-clad plate. The resin composition comprises the following components: alicyclic epoxy resin, hydrocarbon resin and polyphenyl ether resin, preferably, the alicyclic epoxy resin comprises one or more of alicyclic glycidyl ether and alicyclic glycidyl ester; preferably, the alicyclic epoxy resin accounts for 10-20 parts, the hydrocarbon resin accounts for 20-35 parts, and the polyphenyl ether resin accounts for 50-70 parts. According to the invention, the alicyclic epoxy resin, the hydrocarbon resin and the polyphenyl ether resin are blended for the first time to prepare the resin composition for the white copper-clad plate with low dielectric loss and high Tg, the prepreg and the copper-clad plate, so that the resin has excellent compatibility, the interlayer bonding strength of the prepared plate is greatly improved, and the technical blank in the field is filled up; and higher terminal application requirements can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper-clad laminates, and specifically relates to a resin composition for low-loss and high-Tg white copper-clad laminates, a prepreg, a copper-clad laminate and a preparation method thereof. Background Art

[0002] Light Emitting Diode (LED) is a solid-state semiconductor component that converts light energy into visible light. It has the characteristics of low heat generation, environmental protection, and long service life. As electronic information technology develops in the direction of miniaturization and thinness, light-emitting diodes can be directly attached to PCB boards as components and then packaged for use. With the high frequency and high speed of 5G signal transmission and the high integration of electronic products, the copper clad laminate industry is developing rapidly. As a white copper clad laminate used for encapsulating LEDs, it is required to have high reliability, high heat resistance, good dimensional stability, etc. In addition, it is also required to have high reflectivity, yellowing resistance, moisture resistance and other characteristics, so as to cope with the rapid development requirements of advanced displays represented by light-emitting diode (LED) components.

[0003] At present, alicyclic epoxy resin is the mainstream resin system for making white copper clad laminates, but the laminated boards of this system are accompanied by insufficient performance such as high dielectric constant and dielectric loss. For example, the Chinese patent application (publication number CN116814208A) uses alicyclic epoxy resin, trifunctional epoxy resin and styrene-maleic anhydride as the main body to prepare white copper clad laminates. Although the glass transition temperature has been further improved, the dielectric properties of the board still need to be improved.

[0004] Therefore, it is an urgent need for the current industry development to develop a resin composition for white copper clad laminates that has low loss, high glass transition temperature and other properties and is suitable for high-frequency and high-speed MiniLED and other circuit board backlight applications. Summary of the invention

[0005] The purpose of the present invention is to provide a resin composition, a prepreg and a copper clad laminate for low-loss white copper clad laminate in response to the current problems. The copper clad laminate produced by the present invention has the properties of low loss, high glass transition temperature, high whiteness, etc., and is suitable for circuit boards such as high-frequency and high-speed electronic screens Mini LED.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: The invention provides a resin composition for a white copper clad laminate, comprising the following components: alicyclic epoxy resin, hydrocarbon resin and polyphenylene ether resin; the alicyclic epoxy resin comprises one or more of alicyclic glycidyl ether and alicyclic glycidyl ester.

[0007] Further, the following components are included in parts by weight: 10 to 20 parts of the alicyclic epoxy resin; 20 to 35 parts of the hydrocarbon resin; 50 to 70 parts of the polyphenylene ether resin; The alicyclic epoxy resin includes one or more of poly[(2-oxiranyl)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether and bis(3,4-epoxycyclohexylmethyl)adipic acid.

[0008] Further, the polyphenylene ether resin includes one or more of acrylate-terminated polyphenylene ether, methacrylate-terminated polyphenylene ether and styrene-terminated polyphenylene ether; The hydrocarbon resin includes one or more of polybutadiene, polystyrene, polystyrene-butadiene, polyisobutadiene and polystyrene-isobutadiene.

[0009] Further, the following components are included in parts by weight: 10 to 20 parts of the alicyclic epoxy resin, 20 to 35 parts of the hydrocarbon resin, 50 to 70 parts of the polyphenylene ether resin, 20-40 parts of anhydride curing agent, 10 to 100 parts of filler, Fluorescent whitening agent 0.1-10 parts, Initiator 0.01~5 parts, 80-100 parts of solvent; The total amount of the alicyclic epoxy resin, the hydrocarbon resin, and the polyphenylene ether resin is 100 parts by mass.

[0010] Further, the acid anhydride curing agent includes one or more of styrene maleic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, dodecenyl succinic anhydride, adipic anhydride, polyazelaic anhydride, polysebacic anhydride, trialkyl tetrahydrophthalic anhydride, methylcyclohexenyl tetracarboxylic anhydride, terephthalic anhydride, benzophenone tetracarboxylic anhydride or halogenated anhydride; The initiator comprises one or more of benzoyl peroxide, di-tert-butyl peroxide, dicumyl peroxide, di-tert-butyl peroxide isopropylbenzene and tert-butyl perbenzoate; The filler includes one or more of spherical silicon dioxide, silicon powder, titanium dioxide, aluminum oxide, boron nitride and barium titanate; The fluorescent whitening agent includes one or more of stilbene derivatives, phenylpyrazoline derivatives, benzimidazole derivatives, phenylpyrazole derivatives, coumarin derivatives or naphthalimide derivatives; The solvent includes one or more of acetone, propyl acetate, methyl ethyl ketone, methyl isobutyl ketone, toluene, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide or xylene.

[0011] Accordingly, the present invention also provides a method for preparing the resin composition for the white copper clad laminate as described above, comprising the following steps: S1, adding the solvent to the anhydride curing agent, and mixing evenly to obtain a mixture A; S2, adding the hydrocarbon resin, the alicyclic epoxy resin, the polyphenylene ether resin, the filler and the fluorescent brightener to the mixture A, and mixing them evenly to obtain a mixture B; S3, adding the initiator to the mixture B, and mixing them evenly to obtain the resin composition for the white copper clad laminate.

[0012] Furthermore, the uniform mixing method in step S1 includes stirring; the adding in step S2 includes slowly adding; the uniform mixing method in step S2 includes stirring; and the uniform mixing method in step S3 includes stirring.

[0013] Furthermore, in the preparation method of the resin composition for the white copper clad laminate, the stirring speed in step S1 includes 1500 rpm, and the stirring time includes 60 to 120 minutes; the stirring speed in step S2 includes 1800 rpm, and the stirring time includes 60 minutes; the stirring speed in step S3 includes 1800 rpm, and the stirring time includes 30 minutes.

[0014] Correspondingly, the present invention also provides a prepreg, comprising a reinforcing material and any resin composition for the white copper clad laminate.

[0015] Furthermore, the prepreg is prepared by the following method: the reinforcing material is impregnated in the resin composition for the white copper clad laminate, and the prepreg is obtained after drying; the drying method includes heating.

[0016] Correspondingly, the present invention also provides a copper clad laminate, comprising a copper foil and the above-mentioned prepreg; the copper foil is arranged on at least one side surface of the prepreg; the number of the prepregs includes one or more.

[0017] A preferred method for preparing the copper clad laminate of the present invention comprises the following steps: cutting the prepreg, covering both sides with copper foil, laminating the prepreg, and placing the prepreg in a press for hot pressing and curing.

[0018] Furthermore, in the method for preparing the prepreg, the heating temperature is 140 to 200° C., and the heating time is 2 to 3 minutes.

[0019] Furthermore, in the above-mentioned method for preparing the copper clad laminate, the pressure of the hot pressing curing includes 2 to 6 MPa, the temperature of the hot pressing curing includes 150 to 200° C., and the time of the hot pressing curing includes 60 to 140 min.

[0020] The prepreg and copper-clad laminate prepared by using the resin composition for white copper-clad laminate of the present invention have the performance of low dielectric loss and high Tg.

[0021] Epoxy resin is difficult to blend with hydrocarbon resin and polyphenylene ether system, and the epoxy resin in the present invention is alicyclic epoxy resin which is selected after continuous experiments and exploration. Since it contains aliphatic rings but no aromatic rings, it has good compatibility with hydrocarbon resin. In the test process, other types of epoxy resins except alicyclic epoxy resin are blended with polyphenylene ether resin and hydrocarbon resin, and the system is not compatible, and the interlayer bonding strength of the board is low.

[0022] The present invention has also found the optimal ratio range through long-term research, so that the resin has excellent compatibility, and the resin composition is pre-impregnated with a reinforcing material, and the interlayer bonding strength of the obtained board after baking and pressing is greatly improved. The different proportions of the blended raw materials have a great influence on the processability and performance of the board: adding alicyclic epoxy resin to the formula can improve the yellowing resistance, but excessive addition will increase the thermal expansion coefficient; adding polyphenylene ether resin can increase the glass transition temperature, but excessive addition will cause high viscosity and be unfavorable for processing, and it is easy to accelerate self-polymerization, resulting in poor compatibility of resin components and decreased interlayer bonding strength; if too much hydrocarbon resin is added, although the dielectric properties are enhanced, the low molecular weight and high fluidity of hydrocarbon resin will affect production and processing.

[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention is the first to blend alicyclic epoxy resin, hydrocarbon resin and polyphenylene ether resin to prepare a resin composition for white copper clad laminates, a prepreg and a copper clad laminate, thus filling the technical gap in this subdivided field.

[0024] 2. The present invention achieves an optimal ratio of alicyclic epoxy resin, hydrocarbon resin and polyphenylene ether resin, so that the resins of the resin composition for the white copper clad laminate of the present invention have excellent compatibility with each other, the interlayer bonding strength and other properties of the prepared board are greatly improved, and the reliability of the board is significantly improved.

[0025] 3. In addition to the interlayer bonding strength of the board materials, the prepreg and copper-clad laminate prepared with the white resin composition of the present invention also have high performances such as low dielectric loss, high Tg, and low expansion coefficient, and can meet higher terminal application requirements.

[0026] 4. Through a large number of experiments, we found the appropriate ratio of alicyclic epoxy resin, hydrocarbon resin and polyphenylene ether resin. The resin composition, prepreg and copper clad laminate for white copper clad laminate prepared with this ratio take into account both processability and board performance. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with specific implementation methods. The material information used in the following examples and comparative examples is as shown in Table 1: Table 1

[0028] Example 1 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 20 parts of styrene maleic anhydride and continue stirring for 60 minutes; slowly add 20 parts of polybutadiene, 20 parts of poly[(2-ethylene oxide)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 60 parts of acrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.1 parts of stilbene derivative, stir at a speed of 1800 rpm for 60 minutes; add 0.2 parts of benzoyl peroxide, continue stirring for 30 min, and obtain a resin composition for white copper clad laminate.

[0029] Example 2 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 20 parts of styrene maleic anhydride and continue stirring for 60 minutes; slowly add 20 parts of polystyrene-butadiene, 20 parts of poly[(2-ethylene oxide)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 60 parts of methacrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.1 parts of stilbene derivative, stir at a speed of 1800 rpm for 60 minutes; add 0.3 parts of benzoyl peroxide, continue stirring for 30 minutes, and obtain a resin composition for white copper clad laminates.

[0030] Example 3 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 20 parts of styrene maleic anhydride and continue stirring for 60-120 minutes; slowly add 30 parts of polybutadiene, 20 parts of poly[(2-ethylene oxide)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 50 parts of styrene-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.1 parts of styrene derivative, stir at a speed of 1800 rpm for 60 minutes; add 0.2 parts of benzoyl peroxide, continue stirring for 30 min, and obtain a resin composition for white copper clad laminate.

[0031] Comparative Example 1 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 20 parts of styrene maleic anhydride and continue stirring for 60 minutes; slowly add 20 parts of polybutadiene, 40 parts of poly[(2-oxirane)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 40 parts of acrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.1 parts of stilbene derivative, stir at a speed of 1800 rpm for 60 minutes; add 0.2 parts of benzoyl peroxide, continue stirring for 30 min, and obtain a resin composition.

[0032] Comparative Example 2 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 20 parts of styrene maleic anhydride and continue stirring for 60 minutes; slowly add 20 parts of polybutadiene, 20 parts of bisphenol A epoxy resin, 60 parts of acrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.2 parts of stilbene derivative, stir at a speed of 1800 rpm for 60 minutes, add 0.2 parts of benzoyl peroxide, continue stirring for 30 min, and obtain a resin composition.

[0033] Comparative Example 3 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 35 parts of styrene maleic anhydride and continue stirring for 60 minutes; slowly add 60 parts of polybutadiene, 35 parts of poly[(2-ethylene oxide)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 5 parts of acrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.1 parts of stilbene derivative, stir at a speed of 1800 rpm for 60 minutes; add 1 part of benzoyl peroxide, continue stirring for 30 min, and obtain a resin composition.

[0034] Comparative Example 4 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 20 parts of styrene maleic anhydride and continue stirring for 60 minutes; slowly add 20 parts of polybutadiene, 20 parts of phenolic epoxy resin, 60 parts of acrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.2 parts of stilbene derivative, stir at a speed of 1800 rpm for 60 minutes, add 0.2 parts of benzoyl peroxide, continue stirring for 30 min, and obtain a resin composition.

[0035] Comparative Example 5 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 20 parts of styrene maleic anhydride and continue stirring for 60 minutes; slowly add 20 parts of polybutadiene, 20 parts of bisphenol F epoxy resin, 60 parts of acrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.2 parts of stilbene derivative, stir at a speed of 1800 rpm for 60 minutes, add 0.2 parts of benzoyl peroxide, continue stirring for 30 min, and obtain a resin composition.

[0036] Comparative Example 6 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 5 parts of styrene maleic anhydride and continue stirring for 60 minutes; slowly add 25 parts of polybutadiene, 5 parts of poly[(2-ethylene oxide)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 70 parts of acrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.1 parts of stilbene derivative, stir at a speed of 1800 rpm for 60 minutes; add 0.2 parts of benzoyl peroxide, continue stirring for 30 min, and obtain a resin composition.

[0037] Comparative Example 7 Take 100 parts of N,N-dimethylformamide, keep the rotation speed at 1500 rpm, add 20 parts of styrene maleic anhydride and continue stirring for 60 minutes; slowly add 20 parts of polybutadiene, 20 parts of poly[(2-ethylene oxide)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 60 parts of acrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.1 parts of stilbene derivative, stir at a rotation speed of 1800 rpm for 60 minutes to obtain a resin composition.

[0038] Comparative Example 8 Take 100 parts of N,N-dimethylformamide, slowly add 20 parts of polybutadiene, 20 parts of poly[(2-ethylene oxide)-1,2-cyclohexanediol] 2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether, 60 parts of acrylate-terminated polyphenylene ether, 100 parts of titanium dioxide and 0.1 parts of stilbene derivative, and stir at a speed of 1800 rpm for 60 minutes; add 0.2 parts of benzoyl peroxide, continue stirring for 30 min, and obtain a resin composition.

[0039] Effect example The resin compositions obtained in the above Examples 1 to 3 and Comparative Examples 1 to 8 were tested for their effects in the following steps: 1. Preparation of prepregs: impregnate each group of resin compositions with a reinforcing material, wherein the reinforcing material is 2116 specification E-Glass, and bake in an oven at 171°C for 2 to 3 minutes to obtain each group of prepregs; 2. Preparation of copper clad laminates: After stacking 6 prepregs, each group is covered with a 1 oz copper foil on the top and bottom, and then put into a hot press at 2-6 MPa and 170°C for 60 min, and cooled naturally to obtain each group of laminates (copper clad laminates); 3. Performance test: The minimum dynamic viscosity is tested with prepreg as the sample, and other items are tested with laminate as the sample.

[0040] The test methods for each project are as follows: (1) Glass transition temperature (Tg): measured by differential scanning calorimetry (DSC) according to the DSC method specified in IPC-TM-650 2.4.25.

[0041] (2) Dielectric loss (Df): Tested according to IPC-TM-650 2.5.5.9 method, frequency is 3GHz.

[0042] (3) Whiteness: The L value of the sample for measurement at 450 nm was measured using a spectrocolorimeter in accordance with JIS Z-8722 to indicate the initial whiteness.

[0043] (4) Reflectance: The reflectance of the measurement sample at 450 nm was measured using a spectrocolorimeter in accordance with JIS Z-8722.

[0044] (5) Interlayer bonding strength: After burning the copper foil on the surface of the copper clad laminate sample (5 mm wide and 150 mm long) by flame for about 20 mm, manually tear the copper foil on both sides of the sample apart by at least 40 mm. Fix the torn sides of the sample strip in the upper and lower clamping surfaces of the material testing machine, set the initial clamp spacing to 30 ± 0.5 mm, and peel at least 50 mm at a 180-degree stretching rate of 50 mm / min. Record the stable minimum peel force. The minimum peel force divided by the sample width is taken as the interlayer bonding strength of the sample.

[0045] (6) Thermal stratification time (T-288): Determined according to IPC-TM-650 2.4.24.1 method.

[0046] (7) Water absorption rate: The sample with copper foil removed from both sides was cooked in a pressure cooker at 121°C and 105 kPa for 1 hour. The water absorption rate was calculated based on the weight before and after cooking.

[0047] (8) Z-axis CTE: Tested according to IPC-TM-650 2.4.24 method.

[0048] (9) Minimum dynamic viscosity: Grind the prepreg into powder and measure the viscosity using a viscometer according to GB / T 265-1988.

[0049] The test results of the embodiments and comparative examples are shown in Table 2 and Table 3.

[0050] Table 2

[0051] Table 3

[0052] The test results in Table 2 and Table 3 are analyzed as follows: Examples 1 to 3 all have high Tg, low dielectric loss and high whiteness.

[0053] Comparative Examples 2, 4, and 5 are compared with Examples 1 to 3. No alicyclic epoxy resin is added, but bisphenol A epoxy resin, novolac epoxy resin, and bisphenol F epoxy resin are used. The dielectric loss of the prepared copper clad laminate is high, and the glass transition temperature is low. At the same time, the resin compatibility is poor, and the interlayer bonding strength decreases. It can be seen that the resin composition for white copper clad laminate prepared by compounding alicyclic epoxy resin with hydrocarbon resin and polyphenylene ether resin in the present invention has excellent resin compatibility, and the overall performance of the plate is better. It is speculated that since alicyclic epoxy resin contains aliphatic rings but does not contain aromatic rings, it is better than bisphenol A epoxy resin, novolac epoxy resin or bisphenol F epoxy resin in compatibility with hydrocarbon resin.

[0054] Compared with Examples 1 to 3, when the amount of alicyclic epoxy resin added is too much or too little, the prepared copper clad laminates have poor compatibility and the interlayer bonding strength decreases seriously. Among them, when the alicyclic epoxy resin is added too much (Comparative Example 1), the Z-axis CTE is higher than that of the embodiment, so the dimensional stability is slightly worse. When the alicyclic epoxy resin is added too little (Comparative Example 6), the glass transition temperature and dielectric loss are still not as good as those of the embodiment. Compared with Examples 1 to 3, since the ratio of alicyclic epoxy resin, hydrocarbon resin and polyphenylene ether resin is not within the appropriate range, although the whiteness, Z-axis CTE, water absorption, etc. of the prepared copper clad laminate are basically equivalent to those of the embodiment, the resin compatibility is poor, the interlayer bonding strength is low, and it is speculated that because too much hydrocarbon resin is added, its minimum dynamic viscosity is much lower than that of the embodiment, so there is an obvious processability problem.

[0055] Compared with Examples 1 to 3, in Comparative Example 7, a curing agent was used alone without adding an initiator, resulting in the alicyclic epoxy resin and the polyphenylene ether resin reacting completely first, and the hydrocarbon resin did not participate in the reaction because the chemical bonds were not opened in time, resulting in poor performance of the board; Compared with Examples 1 to 3, in Comparative Example 8, an initiator was used alone without adding a curing agent, resulting in the hydrocarbon resin and the polyphenylene ether resin reacting first, and the alicyclic epoxy resin was difficult to cross-link and cure due to lack of a curing agent, resulting in poor compatibility of the resin components and decreased performance in all aspects.

[0056] In summary, the resin composition for white copper-clad laminate prepared by the ratio obtained by a large number of experiments in the present invention has excellent resin compatibility, so the interlayer bonding strength of its board is higher, the T-288 time is longer, and the overall performance of its board is better, while the processing performance of the resin and the prepreg itself has more significant advantages. The copper-clad laminate obtained by the resin composition for white copper-clad laminate of the present invention not only has high whiteness and high reflectivity, but also has lower dielectric loss and high glass transition temperature and other properties, so that it can not only meet Mini LED applications, but also can be used in high-frequency and high-speed fields.

[0057] The above disclosure is only the preferred embodiment of the present invention, which cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A resin composition for a white copper-clad laminate, characterized in that: The invention comprises the following components: alicyclic epoxy resin, hydrocarbon resin and polyphenylene ether resin; the alicyclic epoxy resin comprises one or more of alicyclic glycidyl ether and alicyclic glycidyl ester.

2. The resin composition for white copper-clad laminate according to claim 1, characterized in that: The composition comprises the following components in parts by weight: 10 to 20 parts of the alicyclic epoxy resin; 20 to 35 parts of the hydrocarbon resin; 50 to 70 parts of the polyphenylene ether resin; The alicyclic epoxy resin includes one or more of poly[(2-oxiranyl)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether and bis(3,4-epoxycyclohexylmethyl)adipic acid.

3. The resin composition for white copper-clad laminate according to claim 1, characterized in that: The polyphenylene ether resin includes one or more of acrylate-terminated polyphenylene ether, methacrylate-terminated polyphenylene ether and styrene-terminated polyphenylene ether; The hydrocarbon resin includes one or more of polybutadiene, polystyrene, polystyrene-butadiene, polyisobutadiene and polystyrene-isobutadiene.

4. The resin composition for white copper-clad laminate according to claim 1, wherein: The composition comprises the following components in parts by weight: 10 to 20 parts of the alicyclic epoxy resin, 20 to 35 parts of the hydrocarbon resin, 50 to 70 parts of the polyphenylene ether resin, 20-40 parts of anhydride curing agent, Filler 10-100 parts, Fluorescent whitening agent 0.1-10 parts, Initiator 0.01~5 parts, 80-100 parts of solvent; The total amount of the alicyclic epoxy resin, the hydrocarbon resin, and the polyphenylene ether resin is 100 parts by mass.

5. The resin composition for white copper-clad laminate according to claim 4, characterized in that: The acid anhydride curing agent includes one or more of styrene maleic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, dodecenyl succinic anhydride, adipic anhydride, polyazelaic anhydride, polysebacic anhydride, trialkyl tetrahydrophthalic anhydride, methylcyclohexenyl tetracarboxylic anhydride, terephthalic anhydride, benzophenone tetracarboxylic anhydride or halogenated anhydride; The initiator comprises one or more of benzoyl peroxide, di-tert-butyl peroxide, dicumyl peroxide, di-tert-butyl peroxide isopropylbenzene and tert-butyl perbenzoate; The filler includes one or more of spherical silicon dioxide, silicon powder, titanium dioxide, aluminum oxide, boron nitride and barium titanate; The fluorescent whitening agent includes one or more of stilbene derivatives, phenylpyrazoline derivatives, benzimidazole derivatives, phenylpyrazole derivatives, coumarin derivatives or naphthalimide derivatives; The solvent includes one or more of acetone, propyl acetate, methyl ethyl ketone, methyl isobutyl ketone, toluene, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide or xylene.

6. A method for preparing a resin composition for a white copper-clad laminate as claimed in claim 4, characterized in that: The steps include: S1, adding the solvent to the anhydride curing agent, and mixing them evenly to obtain a mixture A; S2, adding the hydrocarbon resin, the alicyclic epoxy resin, the polyphenylene ether resin, the filler and the fluorescent brightener to the mixture A, and mixing them evenly to obtain a mixture B; S3, adding the initiator to the mixture B, and mixing them evenly to obtain the resin composition for the white copper clad laminate.

7. The preparation method according to claim 6, characterized in that: The method of uniformly mixing in step S1 includes stirring; the adding in step S2 includes slowly adding; the method of uniformly mixing in step S2 includes stirring; the method of uniformly mixing in step S3 includes stirring.

8. A prepreg, characterized in that: The invention comprises a reinforcing material and a resin composition for a white copper clad laminate as claimed in any one of claims 1 to 5.

9. The prepreg according to claim 8, characterized in that: The prepreg is prepared by the following method: the reinforcing material is impregnated in the resin composition for the white copper clad laminate, and the prepreg is obtained after drying; the drying method includes heating.

10. A copper clad laminate, characterized in that: It comprises copper foil and the prepreg according to claim 8; the copper foil is arranged on at least one side surface of the prepreg; the number of the prepregs includes one or more.

Citation Information

Patent Citations

  • Glue for producing white copper-clad plate with high heat resistance and high reflectivity and product thereof

    CN116814208A